Mendiagnosis Masalah Belajar Siswa dalam Konteks Menajemen Kelas: Bagaimana Pengajaran Guru Mereduksinya? - Adetya Dewi Wardani; Imam Gunawan (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Abstract: Student learning problems pose a particular challenge to teachers, as unlike most conditions in the mainstream, the diagnostic process required to some extent depends on teacher interpretation and the teacher-student relationship. The purpose of this study is to diagnose student learning problems in the context of classroom management for the effectiveness of teacher teaching. A qualitative methodology in the form of a grounded theory approach is applied because the purpose of this research is to produce contemporary theories to better understand student learning problems. The participants and the researchers conducted interviews and focus group discussions. The size of the informants of this study is based on theoretical saturation. Transcriptions of interviews, observations, and focus group discussions were subjected to coding (open coding, axial coding, and selective coding) to unlock data-based concepts. We then integrated these concepts into classroom management theory. The results found that student learning problems were categorized into four categories: attitudes, relationships with students and parents, material content, and 21st century skills. This new understanding provides scholars and practitioners with insight into studying student learning problems. Keywords: student learning problems, classroom management, teaching effectiveness, qualitative studies, grounded theory Abstrak: Masalah belajar siswa menimbulkan tantangan khusus bagi guru, karena tidak seperti kebanyakan kondisi pada arus utama, proses diagnostik diperlukan sampai batas tertentu bergantung pada interpretasi guru dan relasi guru-siswa. Tujuan penelitian ini adalah mendiagnosis masalah belajar siswa dalam konteks menajemen kelas untuk keefektifan pengajaran guru. Metodologi kualitatif berupa pendekatan grounded theory diterapkan karena tujuan dari penelitian ini adalah untuk menghasilkan teori kontemporer untuk lebih memahami masalah belajar siswa. Para partisipan bersama peneliti menyelenggarakan wawancara dan focus group discussions. Ukuran informan studi ini berdasarkan kejenuhan teoritis. Transkripsi wawancara, observasi, dan focus group discussions menjadi sasaran pengkodean (open coding, axial coding, dan selective coding) untuk membuka konsep yang didasarkan pada data. Konsep tersebut kemudian kami diintegrasikan ke dalam teori manajemen kelas. Hasilnya menemukan bahwa masalah belajar siswa dikategorikan dalam empat kategori: sikap, relasi dengan siswa dan orang tua, konten materi, dan keterampilan abad 21. Pemahaman baru ini memberikan wawasan kepada para sarjana dan praktisi dalam mengkaji permasalahan belajar siswa. Kata kunci: masalah belajar siswa, manajemen kelas, keefektifan pengajaran, studi kualitatif, grounded theory